The Role of Organizational Culture in Business Performance - Cui, Yan (Exploring Science Academic Conference Series, 2026)
Organizational culture is important in determining the performance of business, how the employees behave, innovation and how well the organization functions. The research presents a literature review on the organizational culture and business performance. This research will aim at examining theoretical voices and empirical evidence on organizational culture and business performance. Companies that have strong and adaptive cultures enjoy better performance, innovativeness is enhanced, and employees are more satisfied. The organization culture is also relevant to the digital transformation and technological change whereby the organizations need the ability to be flexible, and cultures that are innovative so as to be competitive. The literature, however, also demonstrates that according to the literature, an organizational culture is not a sole determinant of the business performance since the leadership style, organizational structure, and external environmental factors also influence the performance of the organization. The research emphasizes that organizational culture is a significant strategic tool, which the organization can utilize in enhancing performance, innovation, and competitiveness.